Emergent Arboviruses: A Review About Mayaro virus and Oropouche orthobunyavirus - Pereira, Thiago Nunes; Virginio, Flávia; Souza, Julia Isabela; Moreira, Luciano Andrade (Frontiers in Tropical Diseases, 2021)
Arthropod-borne viruses have a significant impact on public health worldwide, and their (re) emergence put aside the importance of other circulating arboviruses. Therefore, this scoping review aims to identify and characterize the literature produced in recent years, focusing on aspects of two arboviruses: Mayaro virus and Oropouche orthobunyavirus. The Mayaro and Oropouche viruses were isolated for the first time in Trinidad and Tobago in 1954 and 1955, respectively, and have more recently caused numerous outbreaks. In addition, they have been incriminated as candidate diseases for human epidemics. These viruses have been drawing the attention of public health authorities worldwide following recent outbreaks. To determine the global epidemiological profile of these viruses, we used the Dimensions Database, which contains more than 100 million publications. In general, we identified 327 studies published from 1957 to 2020 for Mayaro virus, and 152 studies published from 1961 to 2020 for Oropouche orthobunyavirus. Interestingly, we observed that Mayaro and Oropouche had a significant increase in the number of publications in recent years. Thus, this comprehensive review will be helpful to guide future research based on the identified knowledge gaps.